Breeding terrorism: an anomie’s anatomy of the terrorism in Indonesia - Munajat, Munajat (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2023)
This article investigates the emergence of terrorism in Indonesia through the anomie sociological perspective. The data for this analysis was gathered from various sources, including documents of terrorist attacks in Indonesia from the internet, personal diaries, and interviews with terrorist prisoners. The anomie theory provides a means of analysis to illuminate the understanding of terrorism, its roots, and causes. From the anomie perspective, terrorism is not viewed as a savage group that allows the killing of innocent people nor a political party that wants to destroy and seize the secular government or Western countries. In the Indonesian context, terrorism is just seen as deviant groups or individuals resulted from global capitalism that destroys the equilibrium of the Muslim world. The anomie consists of two distinct forms: the terrorist attacks and the anomic interpretation of the Islamic holy text (Quran and Sunnah). Both conditions result in a threat to the government that they consider as infidel and aligned with the West. The anomie theory provides more promising remedies to abolish terrorism more permanently and to reduce the tensions between the government and the terrorists by proposing social integration and restoring equilibrium in the Muslim world, especially in Indonesia, as a focus for implementing these remedies.